Are mast cells instrumental for fibrotic diseases? - Overed-Sayer, Catherine; Rapley, Laura; Mustelin, Tomas; Clarke, Deborah L. (Frontiers in Pharmacology, 2014)
Idiopathic pulmonary fibrosis (IPF) is a fatal lung disorder of unknown etiology characterised by accumulation of lung fibroblasts and extracellular matrix deposition, ultimately leading to compromised tissue architecture and lung function capacity. IPF has a heterogeneous clinical course; however the median survival after diagnosis is only 3-5 years. The pharmaceutical and biotechnology industry has made many attempts to find effective treatments for IPF, but the disease has so far defied all attempts at therapeutic intervention. Clinical trial failures may arise for many reasons, including disease heterogeneity, lack of readily measurable clinical end points other than overall survival, and, perhaps most of all, a lack of understanding of the underlying molecular mechanisms of the progression of IPF. The precise link between inflammation and fibrosis remains unclear, but it appears that immune cells can promote fibrosis by releasing fibrogenic factors. So far, however, therapeutic approaches targeting macrophages, neutrophils, or lymphocytes have failed to alter disease pathogenesis. A new cell to garner research interest in fibrosis is the mast cell. Increased numbers of mast cells have long been known to be present in pulmonary fibrosis and clinically correlations between mast cells and fibrosis have been reported. More recent data suggests that mast cells may contribute to the fibrotic process by stimulating fibroblasts resident in the lung, thus driving the pathogenesis of the disease. In this review, we will discuss the mast cell and its physiological role in tissue repair and remodelling, as well as its pathological role in fibrotic diseases such as IPF, where the process of tissue repair and remodelling is thought to be dysregulated.